Pharmacokinetics of Meloxicam in Different Animal Species: A Comprehensive Review - Raul de la Puente; Raquel Diez; M. Jose Diez; Nelida Fernandez; Ana M. Sahagun; Jose M. Rodriguez; Juan J. Garcia; Cristina Lopez (Veterinary Sciences)
Meloxicam is a non-steroidal anti-inflammatory in the oxicam group. It has been extensively used in human and veterinary medicine for their anti-inflammatory, analgesic and antipyretic activities. Meloxicam has shown high therapeutic potential for disorders such as osteoarthritis, musculoskeletal disorder, acute respiratory infection, puerperal septicemia, mastitis and mastitis–metritis–agalactia syndrome. Although meloxicam pharmacokinetic has been described for numerous species, no paper summarizes the existing literature on this field. Thus, the aim of this review was to carry out a review of the literature on the pharmacokinetics of meloxicam in different animal species and gather the data in a single review article. A comprehensive review of the available literature in the PubMed, Web of Science and Scopus databases was performed. Meloxicam shows good bioavailability after oral and parenteral administration in most animal species (85–95%), with the lowest values in sheep after oral administration. It presents a rapid distribution with a small volume of distribution, which can be attributed to relatively high ionization state of meloxicam at physiological pH and its high plasma protein binding (close to 99%). It is extensively metabolized in the liver in several inactive polar metabolites, which are excreted, like unchanged meloxicam in urine and feces. Meloxicam also shows a long elimination half-life and low clearance.